New records of Xenanoetus species (Astigmata: Histiostomatidae) in Western Europe, and their association with pig carcasses - Medjedline Hani; Marta I. Saloña-Bordas; M. Alejandra Perotti (Biologia, 2022)
The genus Xenanoetus Mahunka, 1969, only described by the hypopial stage, is characterised by an enlarged gnathosoma, the presence of double claws in legs I, II and III in addition to remarkably broadened femur and genu of legs I and II, particularly visible in lateral view. Only five species from this genus have been described and they are all from the northern hemisphere. Hypopi are generally found as phoretic on Sphaeroceridae flies and Hydrophilidae beetles. Until present, hypopi of the species Xenanoetus grandiceps have only been reported in Mongolia, described by Mahunka in 1973. Xenanoetus grandiceps is characterised by the presence of a pair of arches pointing anteriorly in the posterior part of the gnathosoma. Here we report for the first time X. grandiceps in Spain, and for the second time X. vestigialis. Both species were found in association with carcass remains, as phoretic on lesser dung flies (Sphaeroceridae), which were collected in a mixed deciduous forest near the Atlantic coast. Additional new information on morphological characteristics of these Xenanoetus species, as well as habitat requirements and biology are presented in this report.